Integrated net pay cut-off evaluation workflow for tight sandstone reservoirs: a case study of the Linxing gas field, Ordos Basin - Li, Li; Yu, Jie; Huang, Tao; Tang, Lina; Wei, Dan; Li, Mingyu; Nie, Xin (Frontiers in Earth Science, 2025)
Net pay detection is a crucial stage in reservoir characterization, serving various purposes such as reserve estimation, reservoir modeling, simulation, and production planning. Net pay was quantified through the use of petrophysical cut-offs. However, these cut-offs varied according to core and dynamic data, introducing uncertainty into the evolution process. This challenge was particularly pronounced in tight sandstone reservoirs, characterized by low porosity. In the Linxing gas field of the Ordos Basin, the tight sandstone reservoirs of the Shiqianfeng, upper Shihezi, lower Shihezi, Shanxi, and Taiyuan formations exhibited ultra-low porosity and permeability, thereby complicating the determination of net pay cut-offs. This study utilized extensive data from the Linxing gas field, including core data from 50 wells, gas testing data from 217 wells, and comprehensive well logging and gas logging data. An analysis of the study area’s gas-bearing characteristics was presented, accompanied by a straightforward net pay cut-off evaluation workflow. The shale volume was evaluated to identify the net sand, while porosity and permeability evaluations were conducted to identify the net reservoir. Hydrocarbon saturation analysis was employed to establish net pay. Eight methods were employed to determine the net pay cut-offs. These include the particle size analysis for the shale volume cut-off, statistical accumulation frequency, minimum pore throat radius, mercury injection capillary pressure, gas production per meter index, and cross-plot analysis methods—based on fracturing gas test data—for porosity and permeability cut-offs. The bound water saturation and the relative permeability analysis methods were employed to determine hydrocarbon saturation cut-offs. Subsequently, formations were divided into two vertical sections; the upper section (including the fifth layer of the Shiqianfeng and upper Shihezi formations) is the target section in this study, with net pay cut-offs determined as follows: 20% shale volume, 6% porosity, 0.15 mD permeability, and 40% gas saturation. The net pay cut-offs determined in the upper section were validated against actual production data. This study provides a reliable basis for reserve calculation in the Linxing gas field, offering technical support for future development and production.